2014
DOI: 10.1080/00220388.2014.940913
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of International Remittances on Poverty and Inequality in Ethiopia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 32 publications
(33 reference statements)
2
22
0
1
Order By: Relevance
“…Growing evidence from HH survey data support that international remittances have reduced the incidence and severity of poverty in several low-income countries (Adams, 2004;Beyene, 2014;Chukwuone, 2007;Durand, Parrado & Massey, 1996;Esquivel & Pineda, 2006;Funkhouser, 2006;Gustafsson & Makonnen, 1993;Jones, 1998;Rapoport & Docquier, 2006;Russell, 1986;Taylor, 2006;Taylor et al, 1996;Taylor et al, 2005;UNCTAD, 2011). Specifically, Gustafsson and Makonnen (1993) found international remittances to have more impact on reducing the depth of poverty than on the poverty headcount; in other words, they were really helpful for the poorest of the poor (World Bank, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence from HH survey data support that international remittances have reduced the incidence and severity of poverty in several low-income countries (Adams, 2004;Beyene, 2014;Chukwuone, 2007;Durand, Parrado & Massey, 1996;Esquivel & Pineda, 2006;Funkhouser, 2006;Gustafsson & Makonnen, 1993;Jones, 1998;Rapoport & Docquier, 2006;Russell, 1986;Taylor, 2006;Taylor et al, 1996;Taylor et al, 2005;UNCTAD, 2011). Specifically, Gustafsson and Makonnen (1993) found international remittances to have more impact on reducing the depth of poverty than on the poverty headcount; in other words, they were really helpful for the poorest of the poor (World Bank, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Combining the existing literature on poverty, like Adams (2006), Andersson, Engvall and Kokko (2006), Beyene (2014), Phangaphanga (2013) and Taylor (2006), we draw upon some determinants of poverty for the empirical investigation, including remittances as one of the explanatory variables. The specification is as follows:…”
Section: Model Specificationmentioning
confidence: 99%
“…The micro-level investigation is motivated by the belief that remittances are mostly used for consumption by the remitters family. Using the Ethiopian Urban Socio-Economic Survey, Beyene (2014) documents that receiving remittances is positively influenced by the number of kids, adults, and secondary school graduates, but is negatively affected by the number of household members employed and the number of household members who have completed only primary education. Gupta, Pattillo, and Wagh (2009) used poverty surveys of 76 countries to show that for every 10% increase in the inflow of remittances, there is a 1% fall in headcount poverty and the poverty gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, remittances reduce inequality because their impact is mainly reflected in the poor and negatively correlated with the income of the rich. Beyene (2014) used Ethiopia's 2004 Urban Family Survey to study the impact of remittances on poverty and inequality [8]. It was found that remittances had a significant poverty reduction effect, but did not change inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally speaking, the larger the family's network, the higher the probability of IPTP, but it has no direct impact on family income. The Probit analysis was used to estimate the probabilistic parameters in Equation (8). The estimated results are shown in Table 8.…”
Section: Counterfactual Analysismentioning
confidence: 99%